MODEL KOMUNIKASI RESES ANGGOTA DPRD KOTA PEKANBARU FRAKSI PDIP DAN FRAKSI GOLONGAN KARYA DALAM MENYERAP ASPIRASI MASYARAKAT DI DAPIL II KECAMATAN RUMBAI DAN RUMBAI PESISIR - Amalia, Nadhila Qisthi; Firdaus, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Communication is a basic human activity. Communication can occur in all directions, and in any form. One of the communication that happened to DPRD member and society like recess activity of DPRD member. Members of the DPRD Pekanbaru as a representative of the people have a responsibility to be able to fight for the interests of the people. This study aims to determine the model of communication conducted by Members of Parliament Pekanbaru PDIP Faction Fraction and Faction Golongan Karya in the recess in Dapil II District Rumbai and Rumbai Pesisir, what are the aspirations of the community who became the discussion at the time DPRD Member Pekanbaru PDIP Faction And Fraction Golongan Karya The work of the Reses, and what are the obstacles and supporting factors when DPRD Member Pekanbaru PDI-P Faction and Fraction Golongan Karya Faction conducted arecess. This research uses qualitative method.The subjects of this study consisted of 7 people, 2 Staff Secretariat DPRD Pekanbaru City, 2 Members of DPRD Pekanbaru City and 3 People Society selected by using purposive techniques. This study uses observation data collection techniques, interviews, and research documentation. To achieve the validity of this research data, researchers use extension of participation and triangulation.The results of this study show the first, Communication Model of Members of Parliament Reses Pekanbaru PDI-P Faction and Fraction Golongan Karya In Absorb Aspirations Society with the constituent elements, media and also the response. Second Aspirations of the Community at the recess of Mr. Dapot Sinaga, SE is in the form of making Irrigation Water, Posyandu, and Field Football. While the aspirations of the community in the recess of Ibu Hj. Masny Ernawati is repairing Posyandu floor into ceramic, and Toa. Third, Factors inhibiting the recess of members of DPRD Pekanbaru City Mr. Dapot Sinaga, SE and Mrs. Hj. Masny Ernawati is when there is delay comes at the time of recess activity, and when the power goes out. While the supporting factor of recess activity is the member of DPRD Pekanbaru who carry out the recess has been directly involved in the election and already recognize the surrounding community. The second factor is already served as member of DPRD Pekanbaru City in the previous period.Keywords: Communication, Recess, DPRD Pekanbaru City